Development and implementation of a longitudinal students as teachers program: participant satisfaction and implications for medical student teaching and learning. Issue 1 (December 2017) - Yeung, Celine; Friesen, Farah; Farr, Sarah; Law, Marcus; Albert, Lori
Abstract Background Teaching is a key component of medical practice, but medical students receive little formal training to develop their teaching skills. A longitudinal Students as Teachers (SAT) program was created at the University of Toronto to provide medical students with opportunities to acquire an understanding of educational pedagogy and practice teaching early in their medical training. This program was 7-months in duration and consisted of monthly educational modules, practical teaching sessions, feedback, and reflective exercises. Methods A mixed methods study design was used to evaluate initial outcomes of the SAT program by obtaining the perspectives of 18 second-year medical students. Participants filled out questionnaires at the beginning and end of the 7-month program to indicate their skill level and confidence in teaching. Differences between pre- and post-intervention scores were further explored in a group interview of 5 participants. Results Participants expressed a high degree of satisfaction with the SAT program structure and found the educational modules and practical teaching sessions to be particularly beneficial to their learning. Over the course of the program, there were significant increases in students' confidence in teaching, and self-perceived teaching capacity and communication skills. Furthermore, participants discussed improvements in their effectiveness as learners. Conclusions Teaching is a skill that requires ongoing practice. Our results suggest that a longitudinal program consisting of theoretical modules, practical teaching sessions, feedback, and reflective exercises for medical students may improve teaching and communication skills, and equip them with improved learning strategies. This program also provides students with insight into the experience of teaching while holding other academic and clinical responsibilities.